PENGEMBANGAN SUMBER DAYA APARATUR INSPEKTORAT DAERAH DALAM MENINGKATKAN FUNGSI PENGAWASAN INTERNAL PEMERINTAHAN DAERAH DI KABUPATEN MANGGARAI PROVINSI NUSA TENGGARA TIMUR - Tefa, Gradiana; Hasibuan, Alpius Natanael Jhonhannes (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2020)
The implementation of the regional government is the implementation of all the main tasks and functions of the regional government. In carrying out the main tasks and functions of the regional government, supervision is needed. Supervision is carried out so that the administration of government functions is in accordance with what has been planned and runs according to the established path. This supervision needs to be done by competent people in their field in accordance with the ones being supervised so that the administration of regional government runs as expected. The theory or concept used in this study is a theory according to Robbins regarding the development of apparatus resources which are limited by education and training and also according to Makmur about internal supervision. Internal supervision is seen from repressive supervision and preventive supervision The research results of the authors in the field are that the state civil apparatus in the Manggarai Regency Inspectorate is still very poor in terms of the quantity and quality of the apparatus. The resources of the apparatus at the Inspectorate are still very much needed to be developed so that the implementation of the function of overseeing the implementation of regional government in the Manggarai Regency can be carried out properly and in accordance with what is expected. Even so, the implementation of supervision has been carried out maximally and has good results. This good supervision can be seen from the predicate obtained by Manggarai Regency, namely reasonable exceptions (WDP). This predicate is very good because if you look at the comparison between the apparatus resources the Inspectorate and the objects examined are very striking inequality. Keywords: development, apparatus resource, internal oversight function.